Conceptual skills of people with intellectual disabilities for independent living - Mohd Kamil, Nur Khaleeda; Amin, Aizan Sofia; Md Akhir, Noremy; Ahmad Badayai, Abdul Rahman; Zambri, Insyirah Mohd; Sutan, Rosnah; Khairuddin, Khairul Farhah; Wan Abdullah, Wan Arnidawati (Southwest Jiaotong University, 2024)
In the effort to improve the quality of life of people with intellectual disabilities, the concept of independent living is still a novelty. As most previous research has focused on the concept of independent living among people with disabilities generally, this study will focus on people with intellectual disability (PWID) in particular. Therefore, this study aims to discuss the conceptual skills required by PWID to empower them to live independently. This qualitative study was based on a case study aimed at exploring the conceptual skills needed by people with intellectual disabilities to live independently. A total of 30 informants, including PWID, their mothers, and teachers, were involved in this study. The study results have identified six conceptual skills of PWID toward independent living in terms of financial management, choosing a profession of interest, using public transportation, recognizing one’s abilities and weaknesses, understanding the concept of time, and reading and writing. This study could be used as a new source of reference for PWID, families, and communities in understanding the concept of independent living to improve the quality of life of PWID.